1981
DOI: 10.1021/bi00513a037
|View full text |Cite
|
Sign up to set email alerts
|

Increased translatable messenger ribonucleic acid for argininosuccinate synthetase in canavanine-resistant human cells

Abstract: The level of argininosuccinate synthetase activity in the human tissue culture cell line RPMI 2650 was 6-fold higher when citrulline was substituted for arginine in the culture medium. Canavanine-resistant (Canr) variants were isolated and had enzyme activity up to 25 nmol min-1 (mg of protein)-1 or 180-fold higher than that of the wild-type cells grown in arginine. The differences in enzyme activity were paralleled by differences in the amount of enzyme determined immunologically. The micrograms of enzyme per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…It was previously shown that the human argininosuccinate synthetase gene was not subject to arginine-mediated repression in canavanine-resistant variants of RPMI 2650 cells (11,30). To determine whether the CAT minigenes were capable of showing the appropriate cell-specific regulation, we introduced the CAT minigenes into the Canr-1 cell line (31) using RSVneo as a selectable marker.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…It was previously shown that the human argininosuccinate synthetase gene was not subject to arginine-mediated repression in canavanine-resistant variants of RPMI 2650 cells (11,30). To determine whether the CAT minigenes were capable of showing the appropriate cell-specific regulation, we introduced the CAT minigenes into the Canr-1 cell line (31) using RSVneo as a selectable marker.…”
Section: Methodsmentioning
confidence: 99%
“…Argininosuccinate lyase, which converts argininosuccinate into arginine, is not subject to arginine-mediated repression (11,30). This indicates that the feedback regulation is specific for the argininosuccinate synthetase locus.…”
Section: Human Argininosuccinate Synthetase Minigenesmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar metabolite regulation of AS was observed in cultured human lymphoblasts (10, 11) and in a human epitheloid cell line, RPMI-2650 (18). A second aspect of regulation of AS in cultured cells involves overproduction of the enzyme in cell variants selected for resistance to the toxic arginine analog canavanine (11,18 (Fig. 1).…”
mentioning
confidence: 99%